(untitled) (Journal of actual problems of jurisprudence, 2018)
Issues of ensuring national security relating to aggressive development of the subsoil use sector is one of the strategic tasks of the state. First, a significant option is identifying the level of protection of national interests from potential threats in order to maintain a dynamic development of the society and the state. Secondly, effective management of the economy specifically in the sphere of the use natural resources as well as the state control of compliance with environmental requirements provide ensuring economic and environmental security in the country. However, in the framework of the state’s orientation to maximally use raw material resources for developing the economy causes negative consequences named by the researchers as «resource nationalism» and «resource curse» phenomena. All of the above is the subject of this research. Key words: national security, subsoil use, environmental protection, environmental and economic security, competent (regulatory) authority, «resource nationalism», «resource curse» and investment.